Stream restoration strategies for reducing river nitrogen loads. Issue 10 (1st December 2008) - Craig, Laura S; Palmer, Margaret A; Richardson, David C; Filoso, Solange; Bernhardt, Emily S; Bledsoe, Brian P; Doyle, Martin W; Groffman, Peter M; Hassett, Brooke A; Kaushal, Sujay S; Mayer, Paul M; Smith, Sean M; et al.
Abstract : Despite decades of work on implementing best management practices to reduce the movement of excess nitrogen (N) to aquatic ecosystems, the amount of N in streams and rivers remains high in many watersheds. Stream restoration has become increasingly popular, yet efforts to quantify N‐removal benefits are only just beginning. Natural resource managers are asking scientists to provide advice for reducing the downstream flux of N. Here, we propose a framework for prioritizing restoration sites that involves identifying where potential N loads are large due to sizeable sources and efficient delivery to streams, and when the majority of N is exported. Small streams (1st–3rd order) with considerable loads delivered during low to moderate flows offer the greatest opportunities for N removal. We suggest approaches that increase in‐stream carbon availability, contact between the water and benthos, and connections between streams and adjacent terrestrial environments. Because of uncertainties concerning the magnitude of N reduction possible, potential approaches should be tested in various landscape contexts; until more is known, stream restoration alone is not appropriate for compensatory mitigation and should be seen as complementary to land‐based best management practices.